2021
DOI: 10.1136/bmjspcare-2021-002962
|View full text |Cite
|
Sign up to set email alerts
|

Non-medical devices for chronic breathlessness: use, barriers and facilitators for patients, carers and clinicians - a scoping review

Abstract: BackgroundNon-medical devices such as the handheld fan (fan), mobility aids (wheeled walkers with seats) and inspiratory muscle training (IMT) devices offer benefits for patient management of chronic breathlessness. We examined the published evidence regarding patient, carer and clinician use of the fan, mobility aids and IMT devices for chronic breathlessness management, and the potential barriers and facilitators to day-to-day use in a range of settings.MethodsMEDLINE, Embase, Scopus, EBSCO and the Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
(168 reference statements)
1
5
0
Order By: Relevance
“…However, it seems that current delivery strategies may not always be effective. Our finding that patients believe that a fan is too simple to be credible is consistent with a mixedmethods feasibility RCT [24] where such patient beliefs was a key concern for clinicians implementing the fan influencing uptake and long-term use [27].…”
Section: Plos Onesupporting
confidence: 82%
See 2 more Smart Citations
“…However, it seems that current delivery strategies may not always be effective. Our finding that patients believe that a fan is too simple to be credible is consistent with a mixedmethods feasibility RCT [24] where such patient beliefs was a key concern for clinicians implementing the fan influencing uptake and long-term use [27].…”
Section: Plos Onesupporting
confidence: 82%
“…This was a qualitative in-depth semi-structured interview study. Ethical approval for the study was granted by HYMS Faculty Ethics Committee, University of Hull July 2020 (REF [20][21][22][23][24][25][26][27][28]. The study is reported in accordance with the Consolidated criteria for Reporting Qualitative studies (COREQ) [31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-pharmacologic strategies, the foundation of breathlessness management, 31 are increasingly highlighted in the ILD literature. 32 , 33 A qualitative study of 13 IPF patients described a patient-reported benefit from symptom self-management education, with 80% reporting self-efficacy in symptom management. 26 Nonetheless, they are rarely prescribed in F-ILD in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, real-time patient health monitoring and alarming systems, facilitated by wireless sensor networks and embedded systems, have contributed to improved patient outcomes, especially for those suffering from diseases during their normal life (Al-Aubidy et al, 2016;Orieno et al, 2024). Moreover, the use of non-medical devices for chronic breathlessness, integrated into complex social systems, has highlighted the interactions of patient-carer-clinician triads and their impact on implementation and integration (Prihartadi et al, 2021). Notable lessons learned from embedded systems in medical devices include the importance of trust and security in intelligent embedded systems, particularly in ensuring privacy preservation and user trust (Yadav & Alharbi, 2021;Ezeigweneme et al, 2024).…”
Section: Case Studies and Real-world Examplesmentioning
confidence: 99%

Reviewing the Impact of Embedded Systems in Medical Devices in the Usa

Sedat Sonko,
Ayodeji Matthew Monebi,
Emmanuel Augustine Etukudoh
et al. 2024
imsrj